ПІДГОТОВКА МАЙБУТНІХ ВЧИТЕЛІВ ПОЧАТКОВИХ КЛАСІВ ДО СКЛАДАННЯ ТА СТРУКТУРУВАННЯ НАВЧАЛЬНО-ПІЗНАВАЛЬНИХ ЗАВДАНЬ НА УРОКАХ ЧИТАННЯ (Педагогіка вищої та середньої школи, 2022)
The problems of professional preparation of future teachers of initial classes are explored in the article. The question of drafting and application o f educational-cognitive tasks is lighted to work of students with the texts of textbook on the lessons of reading.